Probucol prevents blood–brain barrier dysfunction and cognitive decline in mice maintained on pro-diabetic diet - Mamo, John; Lam, Virginie; Brook, E.; Mooranian, A.; Al-Salami, Hani; Fimognari, N.; Nesbit, M.; Takechi, Ryu (Sherborne Gibbs Limited, 2018)
© The Author(s) 2018. An emerging body of evidence consistently suggests that compromised blood–brain barrier integrity may be causally associated with cognitive decline induced by type-2 diabetes. Our previous studies demonstrated that selected anti-inflammatory/anti-oxidative agents can preserve the integrity of blood–brain barrier and prevent neuroinflammation in mouse models of dysfunctional blood–brain barrier. Therefore, we have tested whether the previously proven blood–brain barrier protective agent, probucol, can prevent blood–brain barrier breakdown and cognitive decline in a dietary-induced murine model of diabetic insulin resistance. After 6-month chronic ingestion of a diet high in fat and fructose, the mice became insulin resistant. The high-fat and high-fructose-fed mice showed significant cognitive decline assessed by Morris water maze, concomitant with significant elevations in cortical and hippocampal glial acidic fibrillary protein and Fluoro Jade-C staining, indicating heightened neuroinflammation and neurodegeneration, respectively. The integrity of blood–brain barrier in high-fat and high-fructose-fed mice was substantially compromised, and this showed a significant association with heightened neurodegeneration. Co-provision of probucol with high-fat and high-fructose diet completely prevented the cognitive decline and blood–brain barrier dysfunction. Similarly, metformin was able to restore the cognitive function in high-fat and high-fructose-fed mice, while its blood–brain barrier protective effects were modest. These data suggest that probucol may prevent cognitive decline induced by insulin resistance by preserving the integrity of blood–brain barrier, whereas metformin’s neuroprotective effects may be mediated through a separate pathway.